2003
DOI: 10.1002/j.0022-0337.2003.67.12.tb03729.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated External Defibrillator Use Among the General Population

Abstract: Automated External Defibrillators (AED) are becoming more prominent in public locations within the mainstream of our society. They are marketed as providing the ability for a broader range of people, beyond clinicians and community emergency medical services personal, to successfully defibrillate a person in cardiac arrest. The objectives of this study were to determine whether or not a member of the general population, without previous exposure to an AED, could successfully operate an AED, thus delivering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The AED self-instruction card showed impressive ability as a readily available tool to help first-time users to operate AED with better effectiveness. As previous studies have indicated, failure to bare the chest, [16,17] incorrect electrodes placement, [18,19] failure to defibrillate the patient, [20] and lack of awareness to resume CPR after shock, [16,21] were the most common errors in the public usage of AEDs. Thus, the card was designed to emphasize the key points of each step, which proved to be more effective than commercialized AEDs instruction manuals.…”
Section: Discussionmentioning
confidence: 96%
“…The AED self-instruction card showed impressive ability as a readily available tool to help first-time users to operate AED with better effectiveness. As previous studies have indicated, failure to bare the chest, [16,17] incorrect electrodes placement, [18,19] failure to defibrillate the patient, [20] and lack of awareness to resume CPR after shock, [16,21] were the most common errors in the public usage of AEDs. Thus, the card was designed to emphasize the key points of each step, which proved to be more effective than commercialized AEDs instruction manuals.…”
Section: Discussionmentioning
confidence: 96%
“…( 2003 ), Rauner and Bajmoczy ( 2003 ), Roccia et al. ( 2003 ), van Alem et al. ( 2003 ), Portner et al.…”
Section: Pre-ems Servicesunclassified
“…Of note, some studies have shown that the laypersons' ability to understand the instructions and efficiently operate AEDs still need to be enhanced. [9][10][11] It has been reported that laypersons are likely to disregard operation steps such as removing clothes, placing the electrodes, and resuming cardiopulmonary resuscitation (CPR) after the shock. [9] AED training is a good way to cope with improper operation, especially for the reduction of operation time.…”
Section: Introductionmentioning
confidence: 99%